Effect of therapeutic drug monitoring-based dose optimization of piperacillin/tazobactam on sepsis-related organ dysfunction in patients with sepsis: a randomized controlled trial - Hagel, Stefan; Bach, Friedhelm; Brenner, Thorsten; Bracht, Hendrik; Brinkmann, Alexander; Annecke, Thorsten; Hohn, Andreas; Weigand, Markus; Michels, Guido; Kluge, Stefan; Nierhaus, Axel; Jarczak, Dominik; et al. (Intensive care medicine, 2022)
Purpose Insufficient antimicrobial exposure is associated with worse outcomes in sepsis. We evaluated whether therapeutic drug monitoring (TDM)-guided antibiotic therapy improves outcomes. Methods Randomized, multicenter, controlled trial from January 2017 to December 2019. Adult patients ( n = 254) with sepsis or septic shock were randomly assigned 1:1 to receive continuous infusion of piperacillin/tazobactam with dosing guided by daily TDM of piperacillin or continuous infusion with a fixed dose (13.5 g/24 h if eGFR ≥ 20 mL/min). Target plasma concentration was four times the minimal inhibitory concentration (range ± 20%) of the underlying pathogen, respectively, of Pseudomonas aeruginosa in empiric situation. Primary outcome was the mean of daily total Sequential Organ Failure Assessment (SOFA) score up to day 10. Results Among 249 evaluable patients (66.3 ± 13.7 years; female, 30.9%), there was no significant difference in mean SOFA score between patients with TDM (7.9 points; 95% CI 7.1–8.7) and without TDM (8.2 points; 95% CI 7.5–9.0) ( p = 0.39). Patients with TDM-guided therapy showed a lower 28-day mortality (21.6% vs. 25.8%, RR 0.8, 95% CI 0.5–1.3, p = 0.44) and a higher rate of clinical (OR 1.9; 95% CI 0.5–6.2, p = 0.30) and microbiological cure (OR 2.4; 95% CI 0.7–7.4, p = 0.12), but these differences did not reach statistical significance. Attainment of target concentration was more common in patients with TDM (37.3% vs. 14.6%, OR 4.5, CI 95%, 2.9–6.9, p < 0.001). Conclusion TDM-guided therapy showed no beneficial effect in patients with sepsis and continuous infusion of piperacillin/tazobactam with regard to the mean SOFA score. Larger studies with strategies to ensure optimization of antimicrobial exposure are needed to definitively answer the question.